PENERAPAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY TERHADAP PEMBERDAYAAN MASYARAKAT SUKU TENGGER BERBASIS KEARIFAN LOKAL - -, Ratnawati - (Magister Manajemen Universitas Wisnuwardhana, 2015)
Abstract, Local wisdom if it is associated with the implementation of CSR in which companies keep doing activities allow the company to keep and develop their culture, customs and habits of the local community. CSR as a form of community relations program implementation, when aimed at the right stakeholders and done properly, will be able to create a condition for the company. So that the company can carry out its activities better without any barriers that arise from the surrounding environment. The study aims to assess the implementation of CSR on local knowledge possessed at Mount Bromo Tengger tribe with community empowerment based on local wisdom. Four focus refers to the international standards of the successful implementation of CSR set by the Global Reporting Initiatives (GRI) includes: (1) economic development and community empowerment (2) care for environmental protection (3) guarantee the implementation of non-discrimination and respect for human rights ( 4) the implementation of occupational health and safety assurance (5) a harmonious relationship with the community based on the principles of good governance.Keywords: Corporate Social Responsibility, Community Empowerment, Local Wisdom